Loss of excitatory inputs and decreased tonic and evoked activity of locus coeruleus neurons in aged P301S mice - Anthony M. Downs; Gracianne Kmiec; Christina M. Catavero; Luke A. Wykoff; Zoé A. McElligott (Neurobiology of Disease)
Tau pathology in the locus coeruleus (LC) is associated with several neurodegenerative conditions including Alzheimer's disease and frontotemporal dementia. Phosphorylated tau accumulates in the LC and results in inflammation, synaptic loss, and eventually cell death as the disease progresses. Loss of LC neurons and noradrenergic innervation is thought to contribute to the symptoms of cognitive decline later in disease. While loss and degeneration of LC neurons has been well studied, less is known about changes in LC physiology at advanced stages of tau pathology that precedes neurodegeneration. In this study, we investigated the ex vivo electrophysiological properties of LC neurons in male and female mice from the P301S mouse model of tauopathy at 9 months of age, a time-point when significant tau accumulation, cell death, and cognitive impairments are observed. We found a reduction in excitatory inputs and changes in excitatory post-synaptic current kinetics in male and female P301S. There was also a decrease in spontaneous discharge of LC neurons and an increase in AP threshold in P301S mice of both sexes. Finally, we observed a decrease in excitability and increase in rheobase current in P301S mice. Despite the decrease in LC activity in ex vivo slices, we did not identify differences in total tissue norepinephrine (NE) or NE metabolites in prefrontal cortex or hippocampus. Together these findings demonstrate reductions in the activity and excitability of LC neurons at late stages of tau accumulation. However, compensatory mechanisms may maintain normal NE levels in LC projection regions in vivo.